Fixing Onlies Versus Advancing Multiples: Number of Children and Parents’ Preferences for Educational Products - Wang, Phyllis Xue; Liang, Ce; Wang, Qiyuan (Journal of Marketing, 2025)
Due to a continuous decline in fertility rates in recent decades, the number of one-child families has been increasing in both developing and developed countries. Given this significant shift in family structure, it is imperative to investigate the complex dynamics of how the number of children within a family—whether it is a one-child family or a family with multiple children—affects parents’ decision-making in the realm of education. Using a mixed-method approach including seven main studies, among them a secondary data analysis (Study 1) and a field study (Study 2), and four supplementary studies, the authors consistently find that, compared with multichild parents, one-child parents have a stronger relative preference for deficit-based over strength-based educational products. Both mediation and moderation analyses suggest that this effect is driven by one-child parents’ heightened parenting prevention focus. The current research not only enriches our understanding of parenting dynamics, educational decision-making, and parenting regulatory focus but also has implications for a myriad of disciplines, including marketing, psychology, economics, and sociology. More importantly, it carries substantial implications for marketers, educators, and policy makers.